Mineralogy and geochemistry of Mishrif Formation from selected oilfield, south east of Iraq - Taher M. Taha; Enaam J. Abdullah (Tikrit Journal of Pure Science, 2020)
Mishrif Formation (Late Cenomanian) has been studied in four oilfields in southern Iraq, and studied samples were examined by mineralogy and geochemistry analysis using XRF and XRD techniques.